Analisis Kelayakan Investasi Alat Bantu Peras Kedelai di UMKM Susu Kedelai Kabupaten Bekasi - Sholihat, Adinda Shilfiana; Kusnadi, Kusnadi; Putra, Andika Pratama (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Bekasi Soy Milk UMKM Regency face obstacles in increasing production efficiency due to the limitations of manual soybean squeezing tools that are less than optimal. These limitations cause low production capacity and increased labor costs, so that investment in more effective soybean role Assistive tools are essential. This research seeks to evaluate the viability of investing in a soybean squeezing device using the capital budgeting approach by analyzing (NPV), (IRR), and (PP). The analysis results indicate that this investment is viable, with an IRR value of 8.1%, which is greater than (MARR) of 7%. The computation was conducted over a five-year period. using Discounted Cash Flow rates of 7% and 10%. At a discount rate of 7%, a positive NPV value of IDR2,176,495.33 was obtained, while at a discount rate of 10%, a negative NPV value of IDR2,117,136.36 was obtained. In addition, the investment return period or Payback Period is within a reasonable range of 434 days, thus further strengthening the feasibility of using this tool. Thus, the use of soybean squeezing aids is recommended as a solution to increase production efficiency and support the termination of soy milk UMKM businesses. Keywords: Investment Analysis, NPV, Profitability Index,